The neurochemistry of Huntington's disease - Pearson, Sally Jane (1992)
This thesis describes the study of the neurochemistry of Huntington's disease using a large series of post mortem brain tissue taken from patients with Huntington's disease and from matching controls with no previous history of neuropsychiatric disorder. There were two main aims: firstly, to identify and characterise any altered parameters of neurotransmitter systems, especially in relation to the symptomatology of the disease; secondly, to understand the role of neurotoxins in the aetiology of the disease, particularly endogenous compounds that may have derived from aberrant metabolism.